2021
DOI: 10.3390/medicina57020124
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Activation Disorders

Abstract: Background and Objectives: Mast cell disorders comprise a wide spectrum of syndromes caused by mast cells’ degranulation with acute or chronic clinical manifestations. Materials and Methods: In this review article we reviewed the latest findings in scientific papers about mast cell disorders with a particular focus on mast cell activation syndrome and mastocytosis in pediatric age. Results: Patients with mast cell activation syndrome have a normal number of mast cells that are hyperreactive upon stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
(93 reference statements)
0
24
0
Order By: Relevance
“…The typical syndrome is characterized by (1) pathological accumulation of mast cells in organs and tissues and/or (2) aberrant release of ≥mast cell mediators. MCAS are classified as primary clonal (clonal disorders which include systemic mastocytosis and its variants, cutaneous mastocytosis, and the clonal mast cell activating syndrome (CMCAS) or monoclonal mast cell activating syndrome (MMAS)) and the non-clonal mast cell activating syndromes, including secondary, idiopathic, and combined disorders ( Table 1 ) [ 27 , 28 , 52 , 80 , 81 ]. Patients with mastocytosis meet the World Health Organization (WHO) criteria for either cutaneous or systemic disease [ 31 ].…”
Section: Mast Cell Activation Syndromementioning
confidence: 99%
“…The typical syndrome is characterized by (1) pathological accumulation of mast cells in organs and tissues and/or (2) aberrant release of ≥mast cell mediators. MCAS are classified as primary clonal (clonal disorders which include systemic mastocytosis and its variants, cutaneous mastocytosis, and the clonal mast cell activating syndrome (CMCAS) or monoclonal mast cell activating syndrome (MMAS)) and the non-clonal mast cell activating syndromes, including secondary, idiopathic, and combined disorders ( Table 1 ) [ 27 , 28 , 52 , 80 , 81 ]. Patients with mastocytosis meet the World Health Organization (WHO) criteria for either cutaneous or systemic disease [ 31 ].…”
Section: Mast Cell Activation Syndromementioning
confidence: 99%
“…If the basal tryptase level is ≥20.0 ng/ml, the likelihood of systemic mastocytosis is high, and a bone marrow biopsy is warranted. Normal or slightly elevated basal serum tryptase levels (11.5–20.0 ng/ml) do not rule out the diagnosis, and highly sensitive polymerase-chain-reaction techniques for KIT D816V transcripts in peripheral-blood leukocytes could be used to confirm or exclude the clinical suspicion ( 29 ). For patients in whom the KIT mutation is detected in peripheral blood, a bone marrow evaluation is indicated ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, up to 4% of the general population presents a recently described autosomal dominant-inherited genetic feature called hereditary alpha-tryptasemia (HαT) [27,28]. Individuals with this genetic trait have extra copies of the MC tryptase gene TPSAB1 encoding for serum tryptase that result in high baseline serum tryptase level > 8 ng/mL.…”
Section: Diagnostic Issuesmentioning
confidence: 99%
“…Individuals with this genetic trait have extra copies of the MC tryptase gene TPSAB1 encoding for serum tryptase that result in high baseline serum tryptase level > 8 ng/mL. Clinical symptoms in HαT are variable, including flushing, urticaria, and GI manifestations, therefore simulating MC disorders [28]. Interestingly, in this setting of individuals, Hamilton et al recently found an increase in duodenal MCs, usually more than 20 MCs/HPF, in clusters < 15 MCs, but without signs of clonality [29].…”
Section: Diagnostic Issuesmentioning
confidence: 99%